Análisis de las Estrategias Empresariales para el desarrollo del consumo interno y su relación con el consumo de los derivados del Sacha Inchi en la provincia de San Martín, 2013 - Sandoval Saavedra, Ricci Katherine (2014)
This research conducted a study and analysis of business strategies for the development of domestic consumption of derivatives of Sacha lnchi 2013, through the identification of the most salient variables of the consumption function in the field of province of San Martin. It was determined that the main causes of the problem of the low consumption of native culture and healthy local produce , poor product positioning, and especially the poor spread of food potential of Sacha lnchi , being one of the most responsible business strategies used by companies producing derivatives Sacha lnchi in the province. For processing and analysis of the interviews and focus group, a picture of systematic qualitative information was used. And for the surveys, the information obtained was processed in statistical and econometric software such as E -Views, SPSS and excel .C= βo+ β1X1 + β2X2 + β3X3 + β4X4 +Ɛ. Regarding the survey data the following econometric model that relates the variables studied was raised as technical analysis. As this analysis technique, the model of analysis of variance (ANOVA) was applied. In the work done, a literature pesquiza of investigations concerning a matter of habits, consumer behavior, Biocomercio, responsible consumption and Sustainable competitiveness, econometric analysis of product consumption, economic development strategy and marketing, made was made over the years concerning domestic consumption, business strategies, in several countries in Europe, Latin America, Peru and the San Martin region . To this we propose the following hypothesis: business strategies for the development of domestic consumption have been inefficient to generate increased consumption of Sacha lnchi derivatives in the province of San Martín. In the development of the investigation concluded that the companies have not been effective to stimulate domestic consumption, this is because the strategies are not well addressed to the domestic market and even not well segmented according to the characteristics of provincial consumer. That is why the importance of efficient uses of business strategies for the development of domestic consumption of Sacha lnchi derivatives and allow economically efficient and ~effective best practices for sustainable management of bio-business products